Publicyzacja prawa prywatnego — prywatyzacja prawa publicznego w kontekście rozważań nad prawem europejskim - Helios, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
An early classificatory attempt at amost basic distinction is the classical formulation of Ulpian, later codified by Justinian, that “the study of law is divided in two branches; that of public and that of private law. Public law is that which regards the government of the Roman State; private law that which concerns the interests of the individuals.” In the continental legal systems there is the most fundamental distinction between private law and public law. English law, on the contrary, avoids a strict separation of private and public law. In this article the authors presents traditional criteria of the public law/private law divide. One part of this paper is devoted to the problem of interpenetration between public law and private law in the context of the European Union and global economy. In the author’s opinion European law introduces new tensions into our legal understanding of what is “public” and what is “private” law.
Keywords: prawo prywatne; prywatyzacja prawa publicznego